Effects of meal frequency on body composition during weight control in boxers - Iwao, S.; Mori, K.; Sato, Y. (Scandinavian Journal of Medicine & Science in Sports, 1996)
The effects of meal frequency on changes in body composition by food restriction were investigated. Twelve boxers were divided between a two meals day-1 group (the 2M group) and a six meals day-1 group (the 6M group). Both groups ingested 5.02 MJ (1200 kcal) day-1 for 2 weeks. Although there was no difference in change of body weight by food restriction between the two groups, the decrease in lean body mass (LBM) was significantly greater in the 2M group than in the 6M group. The decrease in urinary 3-methylhistidine/creatinine was significantly greater in the 6M group than in the 2M group. These results suggest that the lower frequency of meal intake leads to a greater myoprotein catabolism even if the same diet is consumed. Scand J Med Sci Sports 1996 Oct;6(5):265-72